Upaya Menggunakan Whatsapp Bisnis Dalam Branding Dan Pengembangan UMKM Oleh Mahasiswa KKNT MBKM UPN “Veteran” Jawa Timur - Zumrotul Fitriyah; Natasya Intan Ayu Praditha; Hanif Ardhi Pranata; Galuh Kinanti (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2023)
As long as there is an internet connection, social media can be accessed by anyone, regardless of location or time zone. Small and medium entrepreneurs use social media that is widely accessible, simple, and fast as a marketing medium to be bolder in promoting their products. The material in the UPN "Veteran" UPN "Veteran" East Java Thematic KKN activities is the difficulties faced by MSMEs in developing their businesses which are the inspiration for this article. The purpose of this research activity is to learn more about the importance of digitalization through social media, such as opening shops on Instagram, Tiktok, Facebook and Whatsapp, for businesses that can offer or encourage product sales with the aim of increasing sales turnover. The research method of this article is a qualitative research method arranged descriptively. Furthermore, the task of innovation is needed to encourage organizational progress in expanding market access by using virtual entertainment-based data innovation, especially in the use of WhatsApp Business which can be used as the leading promotional correspondence medium. With the existence of the Thematic Real Work Lecture program, it is hoped that by using social media in the form of WhatsApp Business for counseling and training on MSME development in the areas where the Thematic Real Work Lecture program is being carried out from UPN "Veteran" East Java can educate the wider community about the importance of social media in development business, keep abreast of the times and make the most of it.